Feeding and nutrition management of heat-stressed dairy ruminants. Issue 3 (3rd July 2018) - Conte, Giuseppe; Ciampolini, Roberta; Cassandro, Martino; Lasagna, Emiliano; Calamari, Luigi; Bernabucci, Umberto; Abeni, Fabio
Abstract: Climate change, with a constant increase in the Earth temperature, negatively affects livestock production and health. This paper will focus on the possible nutritional and feeding strategies to mitigate the negative impact of heat stress (HS) on ruminants. The first nutrient interacting with hot weather conditions is fibre and its digestibility. It is well recognised how fibre may affect voluntary dry matter intake (DMI), chewing and ruminating activity. A possible dietary strategy to counteract the reduced DMI under hot environment is represented by the increased diet energy concentration, protein supply and essential aminoacids. Mineral feeding under HS condition must cover the supply of each nutrient as consequence of altered turnover, and the needs related to buffer requirements. Particular interest is growing in the use of Se (Se-yeast), because of its role to support the animal antioxidative defences. Water is a pivotal nutrient to cope with HS in ruminants because it plays a role in animal thermoregulation. Recently, some vitamins and feed additives were studied for their action on the animal physiology to cope with HS. Among vitamins, niacin was tested for its action on the vasodilatation in the mammalian and for its role in lipid metabolism; among feed additives, yeasts and plant extracts may exert a positive action in rumen metabolism as well as in regulation of body temperature.